Temporal Changes in Number of Breeding Individuals of the Amami Tip-nosed Frog - Komine, Hirotaka; Trentin, Bruna Elisa [UNESP] (Herpetological Soc Japan, Kyoto Univ, Graduate Sch Scie, 2020)
Amami tip-nosed frog (Odorrana amamiensis) is an endangered species endemic to Amami-Oshima Island and Tokunoshima Island, in Japan. This species is threatened by invasive species and habitat destruction. Although action is needed to protect them, the breeding ecology of O. amamiensis is poorly understood. A better understanding of its breeding ecology would contribute to conservation efforts. This study reports temporal changes in number of O. amamiensis breeding individuals in Kinsakubaru area, Amami-Oshima Island from the 28 Nov. 2015 to the 5 Dec. 2015. A 20 m transect line was set at a stream to count the number of O. amamiensis individuals at night and during daytime for eight days. Over 200 individuals were observed and many of them were breeding with lively mating calls around the small stream at night for three days. The high density of individuals decreased rapidly afterwards. This is the first report quantifying the temporal changes in number of breeding individuals of O. amamiensis. The species is usually nocturnal, but some individuals were observed at breeding sites during the daytime as well. Field research on O. amamiensis is usually conducted at night, but it can be risky because the nocturnal poisonous snake Habu (Protobothrops flavoviridis) also inhabits Amami-Oshima Island. The results suggested that field research during daytime was relatively safer and perhaps an easier approach to find breeding sites of O. amamiensis compared to searching at night.
Keywords: Amami-Oshima Island; Amami tip-nosed frog; breeding ecology; endangered species; endemic species